The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.5511/plantbiotechnology.26.431
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of raffinose in rice seedlings overexpressing OsWRKY11 in relation to desiccation tolerance

Abstract: We previously reported that transgenic rice (Oryza sativa L.) lines overexpressing OsWRKY11 showed significant desiccation tolerance, as indicated by their slower water loss in detached leaves. Here we examined the contents of sucrose, glucose, fructose and raffinose. Raffinose was shown to accumulate at a significantly higher level in the transgenic plants overexpressing OsWRKY11. Microarray analysis of gene expression profile indicated that the gene expression of Os07g0209100 encoding raffinose synthase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
(22 reference statements)
1
20
0
1
Order By: Relevance
“…Overexpression of WRKY in rice induced expression of galactinol synthase and raffinose synthase genes and also improved drought tolerance [62]. Raffinose may play a protectant role in drying resurrection plants [64].…”
Section: Transcription Factors and The Aba Induction Pathway For Desimentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of WRKY in rice induced expression of galactinol synthase and raffinose synthase genes and also improved drought tolerance [62]. Raffinose may play a protectant role in drying resurrection plants [64].…”
Section: Transcription Factors and The Aba Induction Pathway For Desimentioning
confidence: 99%
“…WRKY transcription factors (TFs) bind to the W box, TTGAC(C/T), in promoters of specific genes to activate their expression [62]. The WRKY TFs occur in developing seed and are key agents in the ABA regulatory pathways that respond to environmental stresses, senescence, dormancy and germination of seeds.…”
Section: Transcription Factors and The Aba Induction Pathway For Desimentioning
confidence: 99%
“…There have been many studies showing that the expression of genes related to biosynthesis of galactinol and raffinose is involved in several stresses, and expression specificity of the GolS genes to different stresses has also been reported in Arabidopsis. In rice, accumulation of raffinose in seedlings overexpressing OsWRKY11, which is related to heat shock and drought stress, was reported (Wu et al, 2009). It has also been reported that raffinose content in cold-tolerant rice was slightly increased by chilling treatment at 13/10 • C for 4 days (Morsy et al, 2007) and that the expression of a GolS homologous gene was induced in rice seedlings exposed to a Abbreviations: AGA, alkaline ␣-galactosidase; GolS, galactinol synthase; ORF, open reading frame; RFO, raffinose oligosaccharide; RS, raffinose synthase; SIP, seed imbibition protein.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of galactinol and raffinose in vegetative tissues of different plant species occurs under cold, heat, drought and osmotic stresses (ElSayed et al 2014;Pastorczyk et al 2014). The concentrations of accumulated galactinol and/or raffinose can be sufficiently high to confirm the osmoprotective role of both galactosides (Sun et al 2013;Wang et al 2012a;Wu et al 2009). However, in dehydrated seedlings of wheat (Bogdan and Zagdańska 2006), winter vetch (Vicia villosa Roth) (Lahuta and Górecki 2011) and pea , the concentration of accumulated raffinose is very low.…”
Section: Introductionmentioning
confidence: 99%